(untitled) (Journal of Sciences & Technology, 2017)
The pseudopotential method (PP), based on Density Functional Theory (DFT) using the Generalized Gradient Approximation (GGA) was applied to investigate the Fe2(Zr, Nb) system within the three Laves phases structures: Cubic C15, Hexagonal C14 and C36. The effects of Nb concentration on structural, thermal and stability of the system were studied. The lattice parameters and bulk modulus of the three phases were predicted and showed a good agreement with the available experimental data. The rigidity of the Fe2Nb was higher than the Fe2Zr one for C15, C14 and C36. The energetic phase diagram of the systems was also established by determining the heat formation of the different phases. The obtained results showed that the Laves phases have close formation energies which suggests that the C15, C14 and C36 phases can co-exist at low-temperature. Finally, the temperature effect on the structural parameters, thermal expansions, heat capacities and Debye temperatures are determined from the non-equilibrium Gibbs functions and discussed accordingly.